Mewujudkan Relasi Harmonis Tuhan-Manusia-Alam Melalui Analisis LQ dan Shift Share Sektor Unggulan Green Campus UIN Raden Intan Lampung - Kaisa Zahwa Azhara; Dea Pitaloka; Sevira Karisma; Tia Hidayah; Felisa Rachma Fadlillah; Dwi Arya Pangestu; Desi Nurhabibah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research is motivated by the important role of Islamic higher education institutions in addressing the global ecological crisis through green campus policies aligned with spiritual values. UIN Raden Intan Lampung, as a pioneer of Green Campus in Indonesia, integrates aspects of environmental sustainability as a theological manifestation. The purpose of this study is to analyze and map the superior sectors of Green Campus that contribute most to realizing a harmonious relationship between God, humans, and nature. The method used is a descriptive quantitative approach with the Location Quotient (LQ) analysis tool to identify the base sectors and Shift Share analysis to observe changes in the growth of the environmental sector competitively. The research findings indicate that integrated waste management, utilization of renewable energy, and expansion of green open spaces at UIN Raden Intan Lampung are base sectors that have high comparative advantages. This integration of campus management has proven to be able to transform the concept of environmental theology into empirical practices that strengthen the collective awareness of the academic community of the responsibility of the caliphate. The implications of this study emphasize that the use of regional economic analysis in an environmental context can be a strategic instrument for universities to optimize sustainable policies. Theologically, the success of this leading sector proves that preserving the campus ecosystem is an effective bridge to achieving sustainable spiritual and ecological harmony